HOW PATHOGENIC BACTERIA PROFIT FROM YOUR STRESS - T. Dumych; N. Yamakawa; A. Sivignon; Julien Bernard; Sebastien G. Gouin (Праці Наукового товариства імені Шевченка. Медичні науки, 2017)
Crohn’s disease (CD) is a life-long chronic disorder characterized by intestinal inﬂ ammation. Current treatments for CD are directed towards abnormal immune responses rather than the intestinal bacteria that trigger intestinal inﬂ ammation. Disease-molecular aspects: Adherent-Invasive Escherichia coli (AIEC) bacteria abnormally colonize the ileal mucosa in a subgroup of CD patients. Here we elucidate mechanisms by which clinical isolates of adherent-invasive Escherichia coli (AIEC) initially penetrate into the epithelial cell layer, replicate, and establish bioﬁ lms in Crohn’s disease. AIEC utilises the type-1 ﬁ mbrial ﬁ mbrial FimH adhesin to bind to oligomannose glycans on the surface of host cells. Oligomannose glycans, exposed on early apoptotic cells, are the preferred binding targets of AIEC, so apoptotic cells serve as entry points for bacteria into the epithelial cell layer. Thereafter, the bacteria propagate laterally in the intercellular epithelial spaces. We demonstrate oligomannosylation at 2 distinct sites of a glycoprotein receptor for AIEC, the carcinoembryonic cell adhesion molecule 6 (CEACAM6 or CD66c) on human intestinal epithelia. The presence of the highest-afﬁ nity binding target of FimH (oligomannose-5 glycan)on CEACAM6 is demonstrated using LCMS/MS. FimH interacts with CEACAM6, which then clusters. As mannose-dependence is omnipresent in microbial infections, this mechanism of colonization could also apply to other adherent-invasive pathogens. Healing from the disease: AIEC can promote or perpetuate chronic inﬂ ammation and are therefore an interesting therapeutic target. Various strategies that target these E. coli strains have been developed to promote their intestinal clearance. Here, we review current AIEC-targeted strategies, especially anti-adhesive strategies that are based on the development of FimH antagonists. We discuss their potential as personalized microbiota-targeted treatments for CD patients abnormally colonized by AIEC.A large panel of mannose-derived FimH antagonists has been tested for their ability to inhibit E. coli adhesion to host cells. Documented reports suggest that monovalent mannosides are promising candidates that could represent a complementary therapeutic strategy to prevent intestinal inﬂ ammation in the E. coli-colonized CD patient subgroup. Ongoing research continues to improve the pharmacokinetic properties of mannosides, and hopefully, clinical trials will be performed in CD patients in the near future.